Tindak Lanjut Hasil Visitasi dalam Meningkatkan Kualitas Pendidikan dan Pengelolaan Satuan Pendidikan di SMKN 1 Petasia Barat, Sulawesi Tengah - Misriyani Misriyani; Yuanita Indriasari (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2026)
This community service program addresses quality improvement challenges identified during the accreditation visitation at SMKN 1 Petasia Barat, Central Sulawesi, particularly related to school management, curriculum relevance, teacher professional development, and student engagement. The program aims to strengthen educational quality and governance through systematic follow-up of visitation results. Grounded in quality assurance theory, continuous improvement, and school-based management, the program employed a data-driven mentoring and participatory facilitation method. The activities included analysis of visitation findings, formulation of a structured follow-up action plan, capacity-building sessions for teachers and educational staff, and stakeholder coordination to support implementation. The findings indicate improved understanding among school stakeholders regarding quality indicators, the availability of a clear and measurable follow-up plan, and increased commitment to continuous quality improvement. The program demonstrates that structured follow-up of accreditation visitation results can function not only as an administrative response, but also as an effective strategy to foster a sustainable quality culture and enhance the relevance of vocational education.